Laboratory Research on a Presumably PK-Gifted Subject - Gimeno, Juan (Journal of Scientific Exploration, 2017)
Between June 2014 and December 2015, a PK laboratory was organized in Buenos Aires. Up to five video cameras were installed to record the events. Various devices were assembled to measure physical, physiological and environmental variables. 23 meetings were held with a presumptive PK subject, identified in previous research. The subject was apparently able to move a table at will, through an alleged "PK force", and the phenomena were documented and recorded on several occasions. Although contactless movement of the table or other objects could not be achieved, muscular effort was ruled out as the cause of the observed movements. One experiment developed by William Crawford was repeated, although Crawford’s results were not replicated. EEGs studies were performed with the subject at rest and also during the production of the phenomena. Unexplained anomalies were observed in the EEG data obtained during the production of the phenomena, and the normal curve of a Random Number Generator also deviated significantly (p = 0.008) during the trials. No variations of electric and magnetic fields were found to be associated with the phenomena. Stephen Braude visited the laboratory and attended 3 meetings.